The Empirical Analysis of Relationship between Exchange Rate Volatility and Stock Prices Volatility, the Combination of Garch and Ardl Models - Maddah, Majid; Mahrou, Mehrnaz (International Journal of Economics, Business and Management Studies, 2016)
Exchange rate is one of the effective factors on stock prices. In this paper has been investigated the effect of informal exchange rate volatility on stock prices volatility based on the daily data from 2007 to 2011 using the General Autoregressive Conditional Heteroscedasticity (GARCH) and Auto Regressive Distributed Lag Model (ARDL) in the Iranian economy empirically. The results from estimated models indicate that the informal exchange rate volatility has a negative and significant effect on stock prices volatility with coefficient (-0.411). Also the error correction coefficient in estimated Error Correction Model (ECM) is (-0.88) that shows is adjusted 84 percent of imposed shock by the informal exchange rate on stock prices in the short term.